2011
DOI: 10.1108/02652321111117494
|View full text |Cite
|
Sign up to set email alerts
|

On the role of SMS for transaction confirmation with IVR telephone banking

Abstract: PurposeThe purpose of this paper is to deliver empirical results on the effects of (out‐of‐band) short message service (SMS) confirmation messages after transactions have been completed in an automated interactive voice response (IVR) telephone banking service. The research seeks to discover if SMS confirmations have a positive effect on customer relationship to furnish evidence for a proposed business case for a multi‐channel banking service. The paper aims to offer results on customer attitude on the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
0
14
0
3
Order By: Relevance
“…This indicates that the ease in using the mobile banking application is able to influence the attitude of sharia bank customers while using the mobile banking application. (Peevers et al 2011) in their research on sms banking which is part of mobile banking, it made customers easier to do transactio. Perceived usefulness has a positive effect on the attitude of using mobile banking.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the ease in using the mobile banking application is able to influence the attitude of sharia bank customers while using the mobile banking application. (Peevers et al 2011) in their research on sms banking which is part of mobile banking, it made customers easier to do transactio. Perceived usefulness has a positive effect on the attitude of using mobile banking.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that the Internet banking channel is the cheapest delivery channel for banking products once established (Pikkarainen et al, 2004;Peevers et al, 2011). Sadeghi and Hanzee (201 O,p.252) reported, "while using Internet banking, financial institutions are able to save considerable operating and marketing costs thus providing banks with economics of scale, and banks have reduced their branch networks and downsized the number of service staff, which has paved the way to self service channels such as Internet banking".…”
Section: Identifying Benefits From Internet Bankingmentioning
confidence: 99%
“…According to Mattila et al (2003) Internet banking services is a fairly new experience to many people, low awareness of Internet banking is a major factor in causing people not to use Internet banking. Peevers et al (2011) found that consumers were unaware of the possibilities and advantages involved with Internet banking. Hence, research findings posit that the amount of information a consumer has about Internet banking has a positive effect on usage of Internet banking.…”
Section: Effect Of Information On Internet Bankingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, restaurants (Guo et al, 2007;Terry, 2009), entertainment (Rau et al, 2006;Bruno, 2005), retail stores (Shankar et al, 2010;Dickinger & Kleijnen 2008), banking (Peevers et al, 2011;Amin & Ramayah, 2010;Rumpa, 2005;Riivari, 2005), groceries (Kowatsch & Maass, 2010), and auto sectors (Chattopadhyay et al, 2010) have been widely cited as industries using text messaging services as part of their marketing campaign. However, research suggests that not all the product/services categories have the same success rate.…”
Section: Consumers' Attitudes Toward Different Text Messaging Servicementioning
confidence: 99%